Determination of important biotechnical characteristics of some safflower (Carthamus tinctorius L.) cultivars - Zeynep Eda Oktay; Ebubekir Altuntaş; Esra Nur Gül (Journal of New Results in Science)
The study aimed to determine the biotechnical characteristics (physical properties, color characteristics, angle of repose, and coefficient of friction) of the seeds of safflower cultivars. Moisture contents of Asal, Balcı, and Dinçer cultivars were determined as 8.64%, 9.52%, and 8.57%, respectively. The width (4.04 mm) of the Dinçer cultivar gave higher values than other cultivars. Statistically significant (p